Urothelial Carcinoma of the Bladder Metastatic to Bone Marrow Presenting as Isolated Thrombocytopenia - Robert C. Chan; Greg L. Hundemer; Amy Tatsas; Michael S. Cookson (The Scientific World Journal)
The skeletal system is a frequent site for metastases of urothelial carcinoma (UC) of the bladder (22–37%). Of those cases involving bone, the marrow is infiltrated in 27% of patients. Imaging modalities, such as X-ray and CT, will detect gross skeletal lesions in the vast majority of these patients with bone marrow involvement, however, most patients with bone involvement are symptomatic at presentation. Additionally, there have been few reports in the literature of bone marrow metastases from UC presenting with isolated thrombocytopenia.